Pengaruh Pembelajaran Model Talking Stick Terhadap Peningkatan Motivasi Dan Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas X Semester 2 Di SMAN 1 Pringgabaya - Ernawati, Eli; Aini, Qurratul (Alpatih Harapan Semesta, 2024)
This study aims to determine the effect of the talking stick learning model on increasing student motivation and learning outcomes in the subject of economics for class X semester 2 at SMAN 1 Pringgabaya in the 2023/2024 academic year. The research method used is Quasi Experiment with a Nonequivalent Control Group Design research design. The sample is a control class of 34 students and an experimental class of 35 students. This research is a quantitative research with an experimental method. Data collection techniques in this study are student motivation questionnaires, learning outcome tests and documentation. Data were analyzed using the t-test analysis technique (independent sample t-test) to test the hypothesis partially, and the f-test analysis (ANOVA) to test the hypothesis simultaneously. The results of the independent test analysis until the t-test on motivation with a t-value of 9.301> 1.996 or a sig value of 0.000 <0.05 and on learning outcomes t count of 2.448> 1.996 or a sig value of 0.015 <0.05. So Ho is rejected and Ha is accepted which means there is a significant partial influence of the talking stick model learning on student motivation and learning outcomes. While the results of the simultaneous test are shown by the results of the F test which shows the F value for the motivation variable of 86.507> 3.98, while for the learning outcome variable the F value is 6.180> 3.98. For the significance value of the motivation variable of 0.000 <0.05 and the learning outcome variable of 0.015 <0.05. So, the results of this study accept the hypothesis simultaneously and state that the Talking Stick model learning together has an effect on motivation and learning outcomes. Thus it can be concluded that the hypothesis is partially and simultaneously accepted